Osteogenesis imperfecta - Muñoz Carbajal, Pedro (1964)
This work aims to study a rare bone condition in our setting as in other countries , and was conducted over a period of three years, by systematic observation of 4 patients admitted to the Hospital of the Child, to which has been added four other patients who have been taken from the Statistical this hospital between the years of 1951-1962 . In all eight patients . In the 4 cases that have followed have been practiced clinical, laboratory and software radio, exhaustively , a therapy indicated by Heys (15 ) having been tested. It also entered the first case of Dentinogenesis Imperfecta, which is described in our environment, associated with this disease . The other 4 patients included in this study were unable to locate them to make them more detailed studies . Unable either to conduct the study from the point of view for lack of endocrine means our hospital. Anabolic is used in a first case , achieving a good apparent result.